Поняття та ознаки державно-правового примусу - Калєніченко, Л. І.; Kalenichenko, L. I.; Калєніченко Лідія Іванівна (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 3 (78). - С. 21-30, 2017)
Виокремлено та проаналізовано основні ознаки державно-правового примусу, сформульовано визначення цього правового явища. Під державно-правовим примусом запропоновано розуміти метод впливу держави на особу та суспільство, який здійснюється через правозастосовну діяльність незалежно від волі та бажання юридично зобов’язаних суб’єктів з метою забезпечення належної реалізації норм права.

The points of view of legal scholars on the content and essence, the legal and social nature of state and legal coercion have been analyzed. The main features of state and legal coercion are as follows: 1) it has a state and legal nature; 2) it is a method of exercising state power and a mean of legal influence on social relations; 3) it is a method of legal regulation, which is applied not only in connection with unlawful conduct, but also in order to prevent the violations of the requirements of the law norms and restoration of violated rights and freedoms; 4) it is used to protect the rights and legitimate interests of a person, society and the state in cases clearly stipulated by the law (in the presence of an appropriate factual basis), only in the form, manner and under the conditions stipulated by the current system of legal norms of the state; 5) it is implemented through law-enforcement activities of the state. State and legal coercion has been defined as a method of influence of the state on a person and society in order to ensure the proper implementation of the law norms, which is carried out through law-enforcement activities, regardless of the will and desire of legally obliged subjects.

Выделено и проанализировано основные признаки государственно-правового принуждения, сформулировано определение данного правового явления. Под государственно-правовым принуждением предложено понимать метод влияния государства на общество, который реализуется через правоприменительную деятельность независимо от воли и желания юридически обязанных субъектов с целью обеспечения реализации норм права.
Понятие и признаки государственно-правового принуждения
Concepts and features of state and legal coercion
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; державно-правовий примус; державний примус; правовий примус; державна влада; метод впливу держави; state and legal coercion; state coercion; legal coercion; state power; state’s method of influence; государственно-правовое принуждение; государственное принуждение; правовое принуждение; государственная власть; метод влияния государства